Effect of Helicobacter Pylori Eradication Treatment on Disease Activity in Patients with Rheumatoid Arthritis - Filiz Sivas; Bedriye Mermerci Başkan; Tankut Köseoğlu; Tuba Güler; Yasemin Pekin Doğan; Kürşat Özoran (Archives of Rheumatology, 2008)
Objective: Helicobacter pylori (H. Pylori) infection is related with gastroduodenal diseases, along with some autoimmune diseases like rheumatoid arthritis (RA). The present study investigated the affect of H. pylori eradication treatment on disease activity in patients with RA. Material and Methods: A total of 50 patients with RA were evaluated by the CLO test and histological examination and divided into 2 groups as H. pylori positive and negative. Eradication treatment was given to the H. pylori positive group for 14 days. Patients in both groups were evaluated in terms of disease activity initially and at the 6th month. Results: The H. pylori positive and negative group consisted of 19 and 31 patients, respectively and these groups were not statistically significantly different in terms of age, disease duration, and gastrointestinal complaints (p>0.05). The evaluation of initial and 6th month clinical and laboratory parameters revealed no significant difference between groups in terms of disease activity (p>0.05). Conclusion: The present study revealed no significant difference between H. pylori positive and negative patients in terms of dyspeptic complaints and disease activity. (Rheumatism 2008; 23: 109-13)